Density Functional Theory (DFT) Study on Molecular Interaction between H2O and Graphene - Daffa Hadyan Akmal; Amrina Mustaqim; Indah Gumala Andirasdini; Septia Eka Marsha Putra (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2026)
Graphene has attracted significant attention as an anode material due to its high surface area and unique electronic properties. This study explores the adsorption behavior of H₂O molecules on graphene using Density Functional Theory (DFT) with the van der Waals density functional (vdW-DF). Various molecular orientations (zero-leg, one-leg, and two-leg) and adsorption sites (top, bridge, hollow) were analyzed. The results show that the most stable configuration is the two-leg orientation at the hollow site, with an adsorption energy of -0.123 eV. The findings suggest that the stability of the adsorbed system is governed more by the interaction between hydrogen atoms and the carbon surface than by the oxygen atom. All stable structures are characterized by adsorption distances between 2.8 and 3.2 A. The interaction is classified as physisorption due to its low energy and minimal charge transfer. These results are consistent with previous studies, confirming the key role of molecular orientation and adsorption site in determining the adsorption behavior of H₂O on graphene.